Relationships Between Reactive Agility Movement Time and Unilateral Vertical, Horizontal, and Lateral Jumps. Issue 9 (September 2016) - Henry, Greg J.; Dawson, Brian; Lay, Brendan S.; Young, Warren B.
Abstract : Abstract: Henry, GJ, Dawson, B, Lay, BS, and Young, WB. Relationships between reactive agility movement time and unilateral vertical, horizontal, and lateral jumps. J Strength Cond Res 30(9): 2514–2521, 2016—This study compared reactive agility movement time and unilateral (vertical, horizontal, and lateral) jump performance and kinetics between dominant and nondominant legs in Australian rules footballers ( n = 31) to investigate the role of leg strength characteristics in reactive agility performance. Jumps involved jumping forward on 1 leg, then for maximum height or horizontal or lateral distance. Agility and movement time components of reactive agility were assessed using a video-based test. Correlations between each of the jumps were strong ( r = −0.62 to −0.77), but between the jumps and agility movement time the relationships were weak ( r = −0.25 to −0.33). Dominant leg performance was superior in reactive agility movement time (4.5%; p = 0.04), lateral jump distance (3%; p = 0.008), and lateral reactive strength index (4.4%; p = 0.03) compared with the nondominant leg. However, when the subjects were divided into faster and slower performers (based on their agility movement times) the movement time was significantly quicker in the faster group ( n = 15; 12%; p < 0.001), but no differences in jump performance or kinetics were observed. Therefore, although the capacity for jumps to predict agility performance seems limited, factors involved in producing superior lateral jump performance in the dominant leg may also be associated with advantages in agility performance in that leg. However, because reactive strength as measured by unilateral jumps seems to play a limited role in reactive agility performance and other factors such as skill, balance, and coordination, and also cognitive and decision-making factors, are likely to be more important.